Enhancing Students’ Speaking Skill through Debate Competition Technique - Fitria Wulan Sari; Agus Supriyadi (Sean Institute, 2021)
This article focuses on describing the use of debate technique to increase students’ speaking skill. The objectives of this study are to describe the implementation of debate technique in teaching speaking and to identify how much students’ speaking skill improvement after being taught by using debate technique, the problem faced by the students and the advantage of using debate technique in speaking class. This study is Classroom Action Research (CAR) which consists of Planning, Acting, Observing, and Reflecting. This research was managed in two cycles. The participants of this research were the seventh grade students in MTs Darul Falah Ternate, North Maluku. The instruments used in this research were observation and test. The result of this study showed that using debate technique can improve students’ speaking skill. This is proven by students’ test score that improved in every cycle. In the first cycle, the students’ mean score was 64,20 and in the second cycle was 80,33. Thus can be concluded that debate is an appropriate technique used to improve students’ speaking skill. The result of this study is beneficial for the teacher who teaches at this class and for all teachers in general to have more appropriate technique in teaching speaking for EFL students. The teachers should implement the innovative teaching techniques like debate technique in order can challenge students to be more active, think critically, foster higher student interest in learning, and motivate students to work, in accordance with the demands of learning in the era of disruption 4.0.